Stability And Thermal Properties Of Hydroxyl Multiwalled Carbon Nanotubes In Different Medium - Abdullah, Amirah (2019)
Nanotechnology has introduce nanofluids as suspension of nanoparticles in the base fluids. The nanoparticles dispersion in fluids due to thermal properties limitation. Hence, inclusion of MWCNT-OH nanoparticles and PVP in base fluids could enhance the thermal properties and the nanofluids stability. Futhermore, the low boiling point and high freezing point of deionized water has causes another problem and be solve by mixed this fluid with ethylene glycol which act as antifreeze fluid. Intention of this research are to investigate the nanofluid dispersion and stability and as well as thermal properties performance. The two-step method is used in formulazation of nanofluid on concentration 0.1 wt% to 1.0 wt% of MWCNT-OH and base fluid deionized water to ethylene glycol ratio is 0:100%, 100:0%, 90:10%, 80:20%, 70:30%, 60:40% and 50:50%. The dispersion process has selected 5 minutes dispersion process as the optimum time in getting better dispersion and stability of nanofluids. The nanofluids has been tested at 6°C, 25°C and 40°C in thermal conductivity and heat transfer coefficient test. In thermal conductivity test, addition of MWCNT-OH in deionized water is the highest thermal conductivity enhancement which 21.21% (0.4 wt%) at 40°C. However, the thermal conductivity decrement also happens on deionized water based nanofluids at range concentration 0.3 wt% and 0.5 wt% till 1.0 wt% at 40°C. Moreover, the thermal conductivity results is fluctuated or inconsistent with increment of temperature and concentration. Hence, it mean thermal conductivity is independent on temperature and concentration. Meanwhile, heat transfer coefficient is increases with increment of temperature and nanoparticles concentration. The highest enhancement of heat transfer coefficient is occurs on ratio 70:30;DI:EG which has 104.3% at 40°C and 1.0 wt%. The overall increment of heat transfer coefficient occurs on 1.0 wt% and 40°C. Only on 0:100; DI:EG, and 60:40; DI EG has the highest enhancement on 25°C. Besides, ethylene glycol based nanofluids has high heat transfer coefficient on 6°C.In specific heat test, addition of MWCNT-OH has decreased the specific heat exclude on 0.8 wt% of ethylene glycol based nanofluids. This test is conducted in room temperature. Based on these results, concentration, nanoparticles properties and coagulation in nanofluids causes specific heat decrement. Whilst, surface energy, nanoparticles size and area are contributed in high specific heat. To sum up, seeding of MWCNT-OH in fluids has enhanced the thermal properties on certain concentration and temperature.